An evaluation of Tshivenda orthography with special reference to PAN South African Language Board spelling rules - Tshikota, Shumani Leonard (My University, 2016)
This study sought to identify problems concerning Pan South African Language Board spelling rules in respect of Tshivenḓa orthography. A qualitative descriptive research method was chosen. The study population consisted of Pan South African Language Board spelling rules. The rules dealt with nine indigenous languages that were Tshivenḓa, isiZulu, Siswati, Sesotho, Setswana, Xitsonga, isiXhosa, isiNdebele and Sesotho sa Leboa. Each of the nine indigenous languages had between 12 and 56 rules. Altogether there were 255 rules which constituted the study population of this project. A small but sufficient sample of about twenty rules in Tshivenḓa orthography was selected. Data were collected by means of unstructured interviews with forty-four purposely selected participants which include linguists as well as document analysis. Ethical considerations were ensured in order to protect participants from any harm or discomfort that might arise from being involved in an investigation. The researcher explained the aim and nature of the study to respondents, to get their informed consent before the interviews. Several strategies to prevent defects, challenges and problems in Tshivenḓa orthography were recommended based on the results. The strategies focused on aspects which deal with spelling and orthography rules. Key concepts: orthography, indigenous languages, rules, writing systems.
Thesis (Ph. D. (Tshivenda)) -- University of Limpopo, 2016.
Keywords: Orthography; Indigenous languages; Writing systems; Orthography and spelling; Venda language -- Orthography and spelling; Spelling ability; Venda language